(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
Sharing the sources of Southeast Asian folklore and folk literature, magical fairy tales of Vietnam and Laos have many similarities in a motif of building orphan characters. Applying structural theory in fairy tales with immutability and changes, the structure of the story is described by a series of events “signs help to make a schematic comparison of the structure of various tales,” (Propp, 1968, p.25) the article studies the magical fairy tale Tam and Cam of Vietnam and the Golden Turtle of Laos to see the similarities and differences in the motif of building orphan characters. The similarities in the motif of building orphan characters such as: story structure, character system, incarnation motif, unique object motif, magical force motif show the common cultural space of the region. However, the difference in the situation of the story and the use of magical forces and elements in the story show the customs, belief characteristics, artistic tastes and cultural identity of each nation.